OPTIMALISASI KEMAMPUAN MATEMATIS SISWA SMK NEGERI 2 PAREPARE MELALUI LITERASI DIGITAL BERBASIS GEMINI - Adhalia H, Nurul Fuady; Tungga , Rifaldy Atlant; Irmayani, Irmayani; Putriani, A. Ika; Zain, Abdul; Akkas, Anrian Bin; Yuliana, Yuliana (Universitas Mataram, 2024)
The rapid advancement of digital technology necessitates an enhancement of digital literacy among the public, especially among vocational high school students. This study aimed to improve the digital literacy competencies of Electronics Engineering students at SMK Negeri 2 Parepare in solving mathematical problems through the utilization of Google Gemini. Initial observations revealed that students exhibited misconceptions and faced challenges in finding accurate information related to mathematical concepts on the internet. This educational initiative was conducted in three distinct phases: preparation, implementation, and evaluation. During the implementation phase, students received interactive training on the utilization of Google Gemini. The evaluation results demonstrated a significant improvement in the students' ability to find relevant information, solve mathematical challenges, and foster a growth mindset towards learning. The application of Google Gemini as an educational tool has proven effective in enhancing students' digital literacy. This underscores the importance of integrating technology into the educational framework to facilitate the advancement of students' competencies in the digital era.